Upaya Meningkatkan Motivasi Belajar Siswa Melalui Implementasi Media Quizizz - Rohmah, Noer (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
Education is not only delivered through traditional patterns, but also requires the use of technology. The development of technology requires the world of education to keep up with developments, especially regarding the use of learning media so that it is not boring. One of the interesting learning media is Quizizz because it is a semi-game and is considered capable of increasing students' learning motivation. The aim of this research is to determine the implementation of Quizizz media in increasing student learning motivation in Islamic Religious Education subjects at SMAS Diponegoro Tumpang and the various factors that influence it. The approach used is qualitative with a case study design whose results include; 1. The steps for using Quizizz are that teachers must have an account first, while students can directly enter the browser and enter the code, 2. Supporting factors for implementing Quizizz are that it looks attractive, there is a competition system, it can be used for team work. The inhibiting factors are that students are often hampered by cellphones, not many teachers know and apply Quizizz in learning. 3. Efforts to overcome obstacles to the implementation of Quizizz are by using the facilities provided by the school, Quizizz itself has upgraded to be better and held training for teachers. The positive implications of this research are as a contribution to thinking in the context of fostering and improving the quality of teaching, both for teachers and educational institutions.